Men’s health behaviors among public safety personnel in Kelantan: a prediction and mediation analysis - Mukhti, Muhammad Iqbal (2024)
Introduction: Men's health behaviors are influenced by masculinity norms, often deterring health-promoting actions and help-seeking. These norms exacerbate the health disparities between men and women. Effective health interventions must challenge these traditional masculinity norms to improve health outcomes for men. Objective: This study involved translating and validating the Malay versions of the Conformity to Masculine Norms Inventory (CMNI-30) and the Health Behavior Inventory-Short Form (HBI-SF), predicting men's health behaviors, and assessing the mediating role of social support in the relationship between masculinity norms and men's health behaviors among public safety personnel in Kelantan. Methods: Conducted in two phases from June to December 2023, validated questionnaires first involved 438 male staff at Hospital Universiti Sains Malaysia. In the second phase, involving 257 public safety personnel, the study assessed predictors and social support's mediating role using regression analysis, confirmatory factor analysis (CFA), and structural equation modeling (SEM), conducted using SPSS, R, and Mplus software. Result: Both questionnaires possessed good psychometric properties generally, though some issues were noted. Poor men's health behaviors involved those who never sought treatment at public healthcare facilities, parental influence, and leisure time, while friends/colleagues and transportation support served as protection. Social support fully mediated the relationship between masculinity norms and health behaviors, nullifying the direct negative impact of these norms. The overall effect demonstrated a significant interplay between masculinity norms, social support, and men’s health behaviors. Conclusion: Health interventions targeting social support can effectively counteract the negative implications of masculinity norms, thereby promoting better health behaviors among men.